Ostreichnion (Dothideomycetes, Ascomycota) en los bosques andino patagónicos (Argentina) - Sanchez, Romina Magali (2018)
The genus Ostreichnion is recorded for the first time in Argentina, with two species. Ostreichnion nova-caesariense is mentioned for the first time in South America, being this the third record in the world of this rare species. Ostreichnion appendiculatum, on Nothofagus pumilio, is proposed as a new species. A key to all species in Ostreichnion is provided.